Research on Rock Resistant Coefficient in Lining Tunnels Based on the Generalized Hoek-Brown Failure Criterion - Shiyue Zhang; Ruiyuan Gao; Qingxiang Meng; Xiaohu Zhang (Geofluids)
Rock resistant coefficient is a key parameter in rock engineering and can reflect the resistance of surrounding rocks. According to the load-structure method, there are many different formulas in the determination of rock resistant coefficient using elasticity or plasticity theory. Based on the generalized Hoek-Brown failure criterion, this paper develops a closed-form formula for calculating the rock resistant coefficient. The sensibility of different parameters on the rock resistant coefficient is also analyzed. The fact shows that the formula is sensitive to a, σc, and Kd comparing with mb and s especially when they are in a low value, laying a foundation for the determination of rock resistant coefficient in similar lining tunnels.